Magnetic Excitation for Coupled Pendulum and Piezoelectric Wave Energy Harvester - Wuwei Feng; Xiang Luo; Shujie Yang; Qingping Zou (Micromachines)
Wave energy is one of the most reliable and promising renewable energy sources that has attracted lots of attention, including piezoelectric wave energy harvesting devices. One of the challenges for piezoelectric wave power generation is the relatively low-frequency wave environments in the ocean. Magnetic excitations are one of the techniques used to overcome this issue. However, there is a lack of understanding of the mechanisms to maximize the electric power output of piezoelectric wave energy harvesters through magnetic excitations. In the present study, magnetic excitation experiments were conducted to investigate the power generation of a coupled spring pendulum piezoelectric energy harvester under various magnetic field conditions. Firstly, the mass of the load magnet that can induce the resonance phenomenon in piezoelectric elements was experimentally determined. Then, the power generation of piezoelectric elements was tested under different excitation magnetic spacings. Finally, the influence of different distribution patterns of excitation magnets on the performance of piezoelectric elements was tested. It was found that under the conditions of a load magnet mass of 2 g, excitation magnet spacing of 4 mm, and two excitation magnets stacked on the inner pendulum, optimum power generation of the piezoelectric wave harvester was achieved with a peak-to-peak output voltage of 39 V. The outcome of this study provides new insight for magnetic excitation devices for piezoelectric wave energy harvesting to increase the feasibility and efficiency of wave energy conversion to electrical energy.